A comparison of the pregnancy outcomes between ultrasound-guided high-intensity focused ultrasound ablation and laparoscopic myomectomy for uterine fibroids: a comparative study. (1st January 2020) - Wu, Guangping; Li, Rong; He, Min; Pu, Yuanfang; Wang, Jishu; Chen, Jinyun; Qi, Hongbo
Abstract: Objective: To compare the pregnancy outcomes between ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation and laparoscopic myomectomy (LM). Materials and methods: This study included 676 women with symptomatic uterine fibroids who wished to become pregnant underwent USgHIFU or LM at three hospitals in China from 1 May 2009 to 31 May 2018. The related information of pregnancy and delivery were followed up and analyzed using the chi-square test and two-sided Student t-test. Results: The median follow-up duration was 5 (1–8) years; 20 patients (2.9%) were lost to follow-up. 320 patients were treated with UsgHIFU, and 336 were treated with LM. Two hundred nineteen (68.4%) women became pregnant after USgHIFU ablation, and 224 (66.7%) became pregnant after LM. Four hundred forty-three patients had 501 pregnancies (natural pregnancies, 405; in vitro fertilisation-embryo transfer pregnancies, 38). Average times to pregnancy were 13.6 ± 9.5 months after USgHIFU and 18.9 ± 7.3 months after LM ( p < 0.05). The rate of cesarean delivery was lower in the USgHIFU group (41.6%) than in the LM group (54.9%) ( p < 0.05). Incidences of placenta increta, placenta previa, and postpartum hemorrhage were low after USgHIFU compared with after LM. Incidences of preterm birth, fetal distress, fetal growth restriction, and puerperal infection were higher after USgHIFU than after LM. There was a risk of uterine rupture after both procedures. Conclusions: Compared with LM, USgHIFU ablation can significantly shorten the time to pregnancy, although pregnancy rates of the two procedures are similar. Some risks in pregnancy and delivery after HIFU should be evaluated and monitored.